Genome-wide identification of long non-coding RNA targets of the tomato MADS box transcription factor RIN and function analysis. (29th October 2018) - Yu, Tongtong; Tzeng, David T W; Li, Ran; Chen, Jianye; Zhong, Silin; Fu, Daqi; Zhu, Benzhong; Luo, Yunbo; Zhu, Hongliang
Abstract: Background and Aims: In recent years, increasing numbers of long non-coding RNAs (lncRNAs) have been identified in humans, animals and plants, and several of them have been shown to play important roles in diverse biological processes. However, little work has been performed on the regulation mechanism of lncRNA biogenesis and expression, especially in plants. Compared with studies of tomato MADS-box transcription factor RIPENING INHIBITOR (RIN) target coding genes, there are few reports on its relationship to non-coding RNAs. The aim of the present study was to identify and explore the specific role of RIN target lncRNAs in tomato fruit development and ripening. Methods: lncRNA targets of RIN were identified by chromatin immunoprecipitation sequencing (ChIP-seq) combined with RNA deep sequencing analysis. Six selected lncRNA targets were validated by quantitative real-time PCR, ChIP and electrophoretic mobility shift assays, and we further confirmed differential expression between wild-type and ripening-deficient mutant fruit, and RIN direct binding in the promoter regions. By means of virus-induced gene silencing (VIGS) assays and a clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) genome editing strategy, the ripening-related function of a specific target lncRNA (lncRNA2155) was studied. Key Results: We identified 187 lncRNAs as direct RIN targets, which exhibited RIN binding sites in their promoters and showed different expression between the wild-type and rin mutant. Six target lncRNAs were shown to bind with RIN directly in their promoters in vivo and in vitro. Moreover, using CRISPR/Cas9 technology to knock out the locus of the target lncRNA2155 indicated that it delayed fruit ripening in tomato. Conclusions: Collectively, these findings provide new insight into RIN in the transcriptional regulation of lncRNAs and suggest that lncRNAs will contribute to a better understanding of the RIN regulatory network that controls fruit ripening.